INFORMATION STREAMS OF LOGISTICAL SYSTEMS - E. N. Zhivitskaya (Системный анализ и прикладная информатика, 2015)
The problem of formalisation and practical realisation of information streams of logistical systems, as the basic component of a separate kind of systems the logistical information systems having the features and properties that allows to investigate them by means of methods, applicable to information systems is considered.